Internal Control and Operational Efficiency - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2018)
We examine whether effective internal control over financial reporting has implications beyond that of financial reporting to firm operational efficiency. We predict and find that operational efficiency, derived from frontier analysis, is significantly lower among firms disclosing material weaknesses in internal control relative to firms with effective control. This result exists even in the years leading up to the disclosure of material weaknesses, but disappears after remediation of the internal control problems, suggesting that the remediation of material weaknesses improves operational efficiency. Overall, our study extends the literature on the reporting effects of strong versus weak internal control, and helps inform the debate over the costs versus benefits of the internal control reporting requirements under the Sarbanes-Oxley Act of 2002.